France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper for France provides an analytical framework to explain the consequences of the downward shift in the unemployment/wages relationship. This framework is also used to analyze possible changes in the equilibrium unemployment rate resulting from cuts in employers' social security contributions and movements in the user cost of capital. The contribution of wage moderation to the reduction in the equilibrium unemployment is quantified. The paper also addresses the question of fiscal benefits of job-rich growth in France during 1997-2000.